2015
DOI: 10.1055/s-0035-1567875
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Parameters of Elderly Female Choir Singers

Abstract: Introduction Due to increased life expectancy among the population, studying the vocal parameters of the elderly is key to promoting vocal health in old age. Objective This study aims to analyze the profile of the extension of speech of elderly female choristers, according to age group. Method The study counted on the participation of 25 elderly female choristers from the Choir of Messianic Church of São Paulo, with ages varying between 63 and 82 years, and an average of 71 years (standard deviation of 5.22). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…Finally, concerning measures in the frequency domain, previous studies using spectral analysis have also shown age-related changes in voice even though with some inconsistency. For instance, in the elderly, the fundamental frequency (f0) decreased [ 64 , 65 , 66 , 67 ], increased [ 68 , 69 , 70 ], or even remain unchanged [ 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, concerning measures in the frequency domain, previous studies using spectral analysis have also shown age-related changes in voice even though with some inconsistency. For instance, in the elderly, the fundamental frequency (f0) decreased [ 64 , 65 , 66 , 67 ], increased [ 68 , 69 , 70 ], or even remain unchanged [ 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differences registered between young and elderly women are also expected, as the loss of vocal flexibility due to laryngeal changes in old age is taken into consideration 21,22 . In chorists, on the other hand, the registered average reach for younger elderly women was of 349.96 Hz, whereas the group of older elderly women had an average value of 348.59 Hz 14 . Hence, it is reinforced the difficulty to reach higher frequencies in old age.…”
Section: Resultsmentioning
confidence: 90%
“…Moreover, it is interesting to notice that elderly chorist women may present an even lower reach, possibly resulting from training. A research has presented average values corresponding to 134.82Hz and 137.28Hz in elderly chorist women of two different age groups 14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations